Synovial sarcoma of the elbow presenting with painful stiffness: a case report. (October 2021) - Nevin, Jennifer L; King, Graham JW
Elbow stiffness is a challenging problem for the upper extremity surgeon to treat. It can significantly impact the patient's function in activities of daily living. While the most common etiologies are post-traumatic or secondary to arthritis, a large variety of etiologies should be considered with atypical presentations. It is important that the upper-extremity surgeon have a systematic approach to the diagnosis and management of elbow contracture in order to ensure malignant processes are considered. We present an unusual case of a young patient with atraumatic, non-arthritic elbow stiffness whose underlying diagnosis was a synovial sarcoma, as well as a review of the literature and differential for elbow stiffness. Level of evidence: IV.